Community Mental Health Care Delivery During the COVID-19 Pandemic: Practical Strategies for Improving Care for People with Serious Mental Illness - Kopelovich, Sarah L.; Monroe-DeVita, Maria; Buck, Benjamin E.; Brenner, Carolyn; Moser, Lorna; Jarskog, L. Fredrik; Harker, Steve; Chwastiak, Lydia A. (Community mental health journal, 2021)
The COVID-19 pandemic has presented a formidable challenge to care continuity for community mental health clients with serious mental illness and for providers who have had to quickly pivot the modes of delivering critical services. Despite these challenges, many of the changes implemented during the pandemic can and should be maintained. These include offering a spectrum of options for remote and in-person care, greater integration of behavioral and physical healthcare, prevention of viral exposure, increased collaborative decision-making related to long-acting injectable and clozapine use, modifying safety plans and psychiatric advance directives to include new technologies and broader support systems, leveraging natural supports, and integration of digital health interventions. This paper represents the authors’ collaborative attempt to both reflect the changes to clinical practice we have observed in CMHCs across the US during this pandemic and to suggest how these changes can align with best practices identified in the empirical literature.